John of Damascus, The Council of Nicaea, and The Islamic Challenge: a Theological Discourse on Christology and its Contemporary Relevance - Amadea Prajna Putra Mahardika (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2025)
John of Damascus (JD), as one of the foremost Christian theologians of the early medieval period, played a crucial role in defending Nicene Christology against theological challenges, particularly from emerging Islamic thought. This article explores the intersection of JD’s theological contributions with the doctrinal affirmations of the First Council of Nicaea, particularly concerning the divinity of Christ, His consubstantiality with God the Father, and His eternal pre-existence. The study contrasts these affirmations with Islamic perspectives that regard Jesus (Isa) as a mere human prophet, distinct from divinity and created rather than eternally begotten. By analyzing JD’s apologetics, this article demonstrates how he sought to uphold Nicene orthodoxy amidst the rise of Islam, which presented a monotheistic framework rejecting Trinitarian theology. Furthermore, the study examines the enduring relevance of JD’s theological approach in contemporary interfaith dialogues between Christianity and Islam, particularly in addressing Christological differences. By revisiting his arguments, this article underscores the significance of historical theological discourses in shaping modern religious discussions and fostering a deeper understanding between Christian and Muslim communities.